Tax Compromise and Tax Amnesty Procedures Implementation (Bulletin of Kharkiv National University of Internal Affairs, 2021)
The research is focused on the problems of legal regulation of certain procedures of tax compromise and tax amnesty. The scientific article`s relevance is justified because certain procedures of tax compromise and tax amnesty should contribute to the balance of legitimate interests of citizens and the state. The purpose of the study is to identify propositions for amending the current legislation of Ukraine, establishing the possibility of reaching a tax compromise or the introduction of a tax amnesty. Scientific works of Ukrainian researchers, laws, and regulations were used in the process of studying the problem.The scientific novelty of this article is to make propositions for the development and adoption of a separate Law of Ukraine "On the Organizational and Legal Framework of Tax Amnesty", which would establish the conditions and procedure for tax amnesty in Ukraine in the future.The procedures of the tax compromise are the submission of documents specified by law to the tax authorities, the decision on the need for an unscheduled documentary audit, approval of the amount of tax liability, and payment of funds by a taxpayer. The procedures for placing funds in special accounts in banks, submitting a declaration to the tax authorities and verifying the sources of receipt of the declared funds are applied during the tax amnesty. The final stage of the tax amnesty is the payment of the fee specified by law. A mandatory condition of the tax amnesty is the release of a taxpayer from criminal liability for tax evasion.The results of the study can be used in lawmaking, law-enforcement practice, and the educational process.